Fitness promotion in college: the relationships among students’ perceived physical literacy, knowledge, and physical fitness - Long, Bin; Liu, Yang; Chen, Senlin; Yang, Yiwu; Tang, Suna; Yang, Jimei; Wang, Yuhuai (Frontiers in Psychology, 2024)
The purpose of this study was to examine the relationships among perceived physical literacy (PPL), knowledge of physical activity and fitness (PAF knowledge), and physical fitness. Methods: Undergraduates (N = 968, female = 414; Mage = 18.64) from a public university in central China completed a simplified Chinese version of the PPL instrument, an online test for PAF knowledge, and seven health-related physical fitness tests. The PPL includes three dimensions: (a) confidence and physical competence, (b) motivation, and (c) interaction with the environment. The fitness tests measured lung capacity, body mass index (BMI), andperformances in 800 (female)/1000 (male) meters run, 50 meters dash (50M), sit-up (female) / pull-up (male), standing long jump (SLJ), and sit-and-reach. Results: PPL and its dimensions significantly predicted six fitness test performances both in male (β: